Group B streptococcal infective endocarditis - Mahmoud Abdelghany; Louis Schenfeld (Elsevier, 2014)
Summary: Streptococcus agalactiae (S. agalactiae), also referred as group B streptococcus (GBS), is an important pathogen in neonates and a rare cause of invasive infection in adults. It is well known that GBS endocarditis is a virulent infection that can cause serious complications. The overall mortality rate remains high despite surgical treatment. We describe a case of native mitral valve endocarditis caused by GBS in an 86-year-old woman treated medically. Keywords: Streptococcus agalactiae, Group B streptococcus, GBS, Infective endocarditis, Vegetation